2019
DOI: 10.1021/acsami.8b22217
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Ion-Migration-Induced Degradation of Ultrabright Perovskite Light-Emitting Diodes

Abstract: Low operational lifetime is a critical issue in perovskite light-emitting diodes. The forward-bias currents for light emission accelerate device degradation, which needs to be identified and understood to be able to improve the device stability. Here, we systematically analyze the degradation mechanism of perovskite lightemitting diodes (PeLEDs) fabricated with a sequential deposition method that produce a compact and pinhole-free perovskite film. The device exhibits an efficient green electroluminescence (pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…The degradation mechanisms of perovskite LEDs are divided into three categories: (i) Ion migration, (ii) electrochemical reactions and (iii) interfacial reactions, as summarized in figure 1. As the first order root cause of device degradation, ion migration inside perovskites can lead to defect migration [41][42][43][44], annihilation and creation of halide Frenkel defects [45][46][47][48][49], modification on charge injection [50][51][52][53][54] and distortion of crystal lattice [35,43,49,55] (figure 1(a)), while ion migration across the interface can lead to corrosion of electrodes [36,[56][57][58][59][60][61] (figure 1(b)). Electrochemical reactions driven by charge injection lead to a decomposition of perovskites into PbI 2 at the anode interface [35,49,62] and a formation of deep traps (Pb 0 interstitials) at the cathode interface [63] (figure 1(c)).…”
Section: Mechanisms Of Device Degradationmentioning
confidence: 99%
“…The degradation mechanisms of perovskite LEDs are divided into three categories: (i) Ion migration, (ii) electrochemical reactions and (iii) interfacial reactions, as summarized in figure 1. As the first order root cause of device degradation, ion migration inside perovskites can lead to defect migration [41][42][43][44], annihilation and creation of halide Frenkel defects [45][46][47][48][49], modification on charge injection [50][51][52][53][54] and distortion of crystal lattice [35,43,49,55] (figure 1(a)), while ion migration across the interface can lead to corrosion of electrodes [36,[56][57][58][59][60][61] (figure 1(b)). Electrochemical reactions driven by charge injection lead to a decomposition of perovskites into PbI 2 at the anode interface [35,49,62] and a formation of deep traps (Pb 0 interstitials) at the cathode interface [63] (figure 1(c)).…”
Section: Mechanisms Of Device Degradationmentioning
confidence: 99%
“…We speculate that this is probably attributed to the fact that Br − ions are more mobile than the I − ions due to the reduced size. Recently, Lee et al reported the direct observation of device degradation induced by Br − ion migrating to the electrode . Moreover, considering the driving voltage of the bromide‐based devices is much higher than the iodide ones, there will be more prominent joule heating effects in bromide‐based devices, which could further accelerate the ion migration, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lee et al reported the direct observation of device degradation induced by Br − ion migrating to the electrode. [52] Moreover, considering the driving voltage of the bromide-based devices is much higher than the iodide ones, there will be more prominent joule heating effects in bromide-based devices, which could further accelerate the ion migration, etc. In this regard, on the one hand, to improve the device stability, more robust interface layers that can block the ions moving toward electrodes, as well as interface layers that can improve the charge injecting for lower driving voltage are required.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…One reason is the degradation of emitting layers caused by ion migration under applied bias. [26] It was suggested that the amine cations coordinate with inorganic halogens by hydrogen bond, and the organic tails self-assemble via van der Waals interactions in nanoplatelets. This natural structure not only improves the intrinsic stability of perovskites but also impedes the ion migration in the out-of-plane direction (Figure 5e).…”
Section: Structure and Optoelectronic Properties Of Nanoplateletsmentioning
confidence: 99%
“…Consequently, the accumulated halide ions will not only result in the degradation of materials, but also lead to the corrosion of metal electrodes. [26] Suppression of ion migration becomes especially imperative to mixed-halide perovskites, because multiple fluorescence peaks originating from different halide domains appear. Unfortunately, up till now, there are no good solutions for hybrid halogen perovskite-based blue LEDs.…”
mentioning
confidence: 99%